Highly Asymmetrical Porphyrins with Enhanced Push–Pull Character for Dye‐Sensitized Solar Cells. Issue 50 (13th November 2013) - Kurotobi, Kei; Toude, Yuuki; Kawamoto, Kyosuke; Fujimori, Yamato; Ito, Seigo; Chabera, Pavel; Sundström, Villy; Imahori, Hiroshi
Abstract A porphyrin π‐system has been modulated by enhancing the push–pull character with highly asymmetrical substitution for dye‐sensitized solar cells for the first time. Namely, both two diarylamino moieties as a strong electron‐donating group and one carboxyphenylethynyl moiety as a strong electron‐withdrawing, anchoring group were introduced into the meso‐positions of the porphyrin core in a lower symmetrical manner. As a result of the improved light‐harvesting property as well as high electron distribution in the anchoring group of LUMO, a push–pull‐enhanced, porphyrin‐sensitized solar cell exhibited more than 10 % power conversion efficiency, which exceeded that of a representative highly efficient porphyrin (i.e., YD2)‐sensitized solar cell under optimized conditions. The rational molecular design concept based on highly asymmetric, push–pull substitution will open the possibilities of further improving cell performance in organic solar cells.